A Descriptive, Cross-Sectional Study of Ugandan Students in Health Care Education regarding Postgraduate Migration and Future Practice. (29th February 2012) - Kasangaki, Arabat; Macnab, Andrew; Gagnon, Faith
Abstract : A growing challenge of globalization is the migration of many healthcare trainees to richer nations when they complete their education. This loss of intellectual capital compromises the ability of low-income countries to provide adequate health care. Despite recognition of this loss most African nations keep no track of those they train. Effective investment in health care demands retention of this resource; the ability to direct healthcare providers where needed; understanding of local factors driving migration, choices regarding postgraduate training abroad, and future practice preference. Self-administered questionnaires were distributed to a random sample of 200 Uganda College of Health Sciences students for anonymous completion; 141 / 200 (70.5%) were completed; 84% of respondents intended to pursue postgraduate studies abroad; 63% to migrate within five years of graduation; 57% to work in urban areas. While partly due to global trends and awareness of international opportunities, this negative trend of migration and shunning rural practice is also influenced by sociopolitical and educational elements within Uganda. One option (adopted elsewhere) is mandatory practice in government community health centers for a period following graduation. But the ethics, consequences, and implications of current international migratory trends need to be addressed locally and by the global medical education community.